Forest Management Plan as an Instrument of Sustainable Forest Management - Szalewska, Małgorzata (Polish Yearbook of Environmental Law, 2017)
Being one of the basic elements of ecosystem forest is considered a public good and as such is subject to detailed legal restrictions. Particular kind of legal instruments of sustainable forest management is the planning instrument. Conducting planned activity is indispensable for effective administration, especially in spheres where both the action and the results pertain to a long term perspective. Implementation, by the Legislator, of sustainable forest management based on the idea of activity which leads to achieving normatively determined state inclines to making use of planning instruments. Indispensability of planning acts in the execution of sustainable forest management has been expressis verbis prejudged by the Legislator in article 7 of AoF, which states that sustainable forest management is executed in compliance with the forest management plan or the simpli2ed forest management plan. 4is solution is considered correct and should be granted an endorsement. Di7cult to accept, however, is the state of legal regulation of forest management plans, which constitute a fundamental instrument for the concept of sustainable forest management. Indeterminacy of legal forms of administrative action upon approving plans, and doubts regarding their legal character do not benefit their functioning resulting in vagueness, which leads to the state of legal uncertainty.